Opportunistic routing algorithm based on trust model for ad hoc network - Bo WANG; Xun-xun CHEN (Tongxin xuebao)
Due to the absence of enough physical protection,dynamic topology,distributed collaboration,the limited bandwidth and computing ability in ad hoc network,traditional routing security mechanism cannot adapt to the design of routing protocols.Recently,opportunistic routing is of the research hotspots,which can cope with the unreliable transmissions to improve throughput of the whole network by exploiting the broadcast nature of the wireless medium and spatial diversity of multi-hop wireless network.The concept of trust-based similarity in opportunistic routing for ad hoc network was incorporated,and a novel trusted opportunistic forwarding model based on trust degree of node and least cost of opportunistic routing were also built.Then a trusted minimum cost routing algorithm (MCOR) was proposed and the correctness and effectiveness of this algorithm from theoretical ana ysis were proved.Finally,MCOR algorithm was verified by simulation and was compared with the classic protocols:ExOR,TAODV and Watchdog-DSR.The simulation results show that MCOR scheme can detect and mitigate node misbehaviors.Furthermore,MCOR scheme outperforms the other protocols in terms of throughput,delay,expected ETX and cost of routing.